Molecular Players in Hematologic Tumor Cell Trafficking - Redondo-Muñoz, Javier; García-Pardo, Angeles; Teixidó, Joaquin (Frontiers in Immunology, 2019)
The trafficking of neoplastic cells represents a key process contributing to progression of hematological malignancies. Diapedesis of neoplastic cells across endothelium and perivascular cells is facilitated by adhesion molecules and chemokines which act in concert in tightly regulated directional motility. Intravital microscopy provides spatio-temporal view of neoplastic cell trafficking, and is crucial for testing and developing therapies against hematological cancers. Multiple myeloma (MM), chronic lymphocytic leukemia (CLL) and acute lymphoblastic leukemia (ALL) are hematological malignancies characterized by continuous neoplastic cell trafficking during disease progression. A common feature of these neoplasias is the homing and infiltration of blood cancer cells into the bone marrow (BM), which favors growth and survival of the malignant cells. MM cells traffic between different BM niches and egress from BM at late disease stages. Besides the BM, CLL cells commonly home to lymph modes (LNs) and spleen. Likewise, ALL cells also infiltrate extramedullary organs, such as the central nervous system, spleen, liver and testicles. The 4 integrin and the chemokine receptor CXCR4 are key molecules for MM, ALL and CLL cell trafficking to and out of the BM. In addition, the CCR7 chemokine receptor controls CLL cell homing to LNs, and CXCR4, CCR7 and CXCR3 contribute to ALL cell migration across endothelia and the blood brain barrier. Some of these receptors are used as diagnostic markers for relapse and survival in ALL patients, and their level of expression allows clinicians to choose the appropriate treatments. In CLL, elevated 4expression is an established adverse prognostic marker, reinforcing its role in the disease expansion. Combining current chemotherapies with inhibitors of malignant cell trafficking could represent a useful therapy against these neoplasias. Moreover, immunotherapy using humanized antibodies, CAR-T cells or immune check-point inhibitors together with agents targeting the migration of tumor cells could also restrict their survival. In this review, we provide a view of the molecular players that regulate the trafficking of neoplastic cells during development and progression of MM, CLL and ALL, together with current therapies that target the malignant cells.